Measuring the technical and scale efficiency of Rio de Janeiro samba schools: a DEA approach - Alexandre de Cássio Rodrigues (Exacta, 2019)
This article aims to measure the technical and scale efficiency of the 12 samba schools that paraded in the Rio de Janeiro Carnival special group in 2017. For this, it was used an output oriented model through the Data Envelopment Analysis technique. The component number of each school was adopted as an input data and, by the oder hand, as the choiced output, three of the nine judged grades questions throughout the parade, were are selected through the Principal Component Analysis method. The results show that only Mocidade showed technical and scale efficiency, so, it is a benchmark for the other samba schools. It was also observed that the global technical inefficiency average, evaluated at 8%, was strongly influenced by the low scale efficiency of the samba schools, which, in the majority, had decreasing scale returns. In light of this, alternatives are presented to increase the samba schools efficiency.